Long-Term Mortality After TAVI for Bicuspid vs. Tricuspid Aortic Stenosis: A Propensity-Matched Multicentre Cohort Study - Gasecka, Aleksandra; Walczewski, Michał; Witkowski, Adam; Dabrowski, Maciej; Huczek, Zenon; Wilimski, Radosław; Ochała, Andrzej; Parma, Radosław; Scisło, Piotr; Rymuza, Bartosz; Zbroński, Karol; Szwed, Piotr; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objectives Patients with bicuspid aortic valve (BAV) stenosis were excluded from the pivotal trials of transcatheter aortic valve implantation (TAVI). We compared the in-hospital and long-term outcomes between patients undergoing TAVI for bicuspid and tricuspid aortic valve (TAV) stenosis. Methods We performed a retrospective registry-based analysis on patients who underwent TAVI for BAV and TAV at five different centers between January 2009 and August 2017. The primary outcome was long-term all-cause mortality. Secondary outcomes were in-hospital mortality, procedural complications, and valve performance. Results Of 1,451 consecutive patients who underwent TAVI, two propensity-matched cohorts consisting of 130 patients with BAV and 390 patients with TAV were analyzed. All-cause mortality was comparable in both groups up to 10 years following TAVI (HR 1.09, 95% CI: 0.77–1.51). Device success and in-hospital mortality were comparable between the groups (96 vs. 95%, p = 0.554 and 2.3 vs. 2.1%, p = 0.863, respectively). Incidence of procedural complications was similar in both groups, with a trend toward a higher rate of stroke in patients with BAV (5 vs. 2%, p = 0.078). Incidence of moderate or severe paravalvular leak (PVL) at discharge was comparable in both groups (2 vs. 2%, p = 0.846). Among patients with BAV, all-cause mortality was similar in self-expanding and balloon-expandable prostheses (HR 1.02, 95% CI: 0.52–1.99) and lower in new-generation devices compared to old-generation valves (HR 0.27, 95% CI 0.12–0.62). Conclusion Patients who had undergone TAVI for BAV had comparable mortality to patients with TAV up to 10 years after the procedure. The device success, in-hospital mortality, procedural complications, and PVL rate were comparable between the groups. The high rate of neurological complications (5%) in patients with BAV warrants further investigation.